Total Proximal Left Anterior Descending Artery Occlusion Presenting as Right Sided Chest Pain with a Misdiagnosis of Costochondritis: A Case Report (Tanzania Medical Journal, 2021)
BackgroundAcute coronary syndrome refers to a group of clinical symptoms consistent with acute myocardial ischemia or infarction that are potentially life threating requiring immediate interventions. Certain proportion of patients can present with atypical symptoms leading to a missed diagnosis associated with devastating outcomes.Case presentationWe present a 60 years’ female of African descent with a medical history of hypertension and type 2 Diabetes mellitus who presented with a 2 months’ history of right-sided anterior chest pain and was diagnosed with costochondritis. Further assessment revealed, normal cardiac markers and an electrocardiogram suggestive of anterior wall myocardial infarction. A coronary computed tomography and cardiac magnetic imaging scans revealed a total occlusion of the proximal left anterior descending artery and a viable myocardium respectively. She underwent successful percutaneous coronary interventions with stenting with complete alleviation of her chest pain. ConclusionsThis case report highlights the importance of having a high index of suspicion in high-risk groups such as older females with co-morbidities presenting with atypical symptoms suggestive of acute coronary syndrome to health care providers. This ensures early diagnosis and provision of appropriate treatment associated with good outcomes. Likewise, the case also advocates on the use of advanced cardiac imaging in patients with inconclusive electrocardiographic and biochemical tests.